CHARACTERIZATION OF ELECTRICAL PARAMETERS FOR TOMATO BATTERIES - Ganjar Maulana, Imam
Tomato plant can be found anywhere and it does not depend on the season. Tomato contains substances such as ascorbic acid, citric acid and chemicals which produce cell energy, under certain conditions these chemicals act as electrolytes which could be used in the Galvani cell system to deliver ions and produce electricity. The lack of knowledge and awareness of renewable energy creates limitations in the new way of clean energy production with simple tools and materials that are already available. Departing of the issue, the research used gondol tomatoes with three levels of maturity as the object of tomato battery research by selecting the most effective electrode pairs from copper, zinc, lead and aluminum. The results of measurements of electric current, voltage and intensity of the LEDs from each level of ripeness of the tomatoes measured are illustrated into the graph and could be used to analyze the electrical parameters of the tomato battery. Cu-Zn metal is the most effective electrode pair in experiments with a voltage of 7.1 V and a current of 31×10-4 mA. The smaller pH of the tomatoes will appear that the greater the voltage and current. The intensity of the LED lights produced by 8 red tomatoes is the same as that of the power supply with a voltage range of 2.55-2.60V with currents 2-7×10-2 mA on the blue LED and 1.95-2.10V with 13,5 - 24,5 × 10-2 mA on the red LED.